Keberadaan Asas Pacta Sunt Servanda dalam Perjanjian Internasional - Harry Purwanto (Fakultas Hukum Universitas Gadjah Mada, 2009)
The pacta sunt servanda is one of universally recognized legal principles by which its existence has been known. Its mere relevance is related to treaty since this principle determines that agreed stipulations concluded among parties become legally binding and cause rights and duties to be fulfilled in good faith manner. As it is recognized and accepted among parties to the treaty, it becomes integral part of the law of the treaty particularly of the law of international treaty. The preamble and Article 26 of the 1969 Vienna Convention on the Law of Treaty and the 1986 Vienna Convention reiterate its legal existence as the guiding principle to make and to implement international treaty. In the Indonesian legal system, the existence of that principle inspires the formation of Article 1338 of Indonesian Civil Code and of Article 4 (1) the Law Number 24 of 2000. It can be concluded firmly that the existence of the pacta sunt servanda has formed and evolved as a legal system including the international law legal system today.